Synthesis and characterization of Ni60-hBN high temperature self-lubricating anti-wear composite coatings on Ti6Al4V alloy by laser cladding. (April 2016) - Lu, Xiao-Long; Liu, Xiu-Bo; Yu, Peng-Cheng; Qiao, Shi-Jie; Zhai, Yong-Jie; Wang, Ming-Di; Chen, Yao; Xu, Dong
Abstract: Ni60-hBN composite coatings with varying hBN content were prepared on Ti6Al4V substrates by laser cladding. The composite coatings with no cracks and few pores are bonded metallurgically with the substrates. The phase composition and microstructure of the composite coatings were investigated. The tribological properties of the composite coatings were evaluated under dry sliding wear test conditions at 20 °C, 300 °C and 600 °C, respectively. The microhardness gradually increased from the bottom to the top of the coating and increased with increasing of hBN content. The laser clad Ni60-10%hBN coating exhibits excellent tribological behavior at high temperatures (300 °C and 600 °C). Highlights: Novel self-lubricating anti-wear composite coatings were fabricated on Ti6Al4V. The coatings mainly consist of reinforced carbides, borides and hBN solid lubricant. The coatings with the addition of hBN possessed superior properties than without.